EVALUASI DAN ANALISIS PROGRAM KEMITRAAN KONSERVASI DI TAMAN NASIONAL BUNAKEN DALAM PENGELOLAAN EKOSISTEM TERUMBU KARANG DI DESA POOPOH KABUPATEN MINAHASA - Nikolas ., Loli; Bobby J. V. Polii; Hengki D. Walangitan (AGRI-SOSIOEKONOMI, 2021)
This study aimed to evaluate the conservation partnership program comprehensively and the factors that affect the achievement of the program inside and outside society related with the programs. This research used a combination of qualitative and quantitative methods in a dominant-less dominant design which was analyzed descriptively. The results showed that conservation partnership program already meets the expectations and needs of the community. In environment aspects shows that cover of coral reefs at the conservation partnership site is in moderate condition (35.28%) if compared to the condition of coral reefs outside the conservation partnership site which is in bad condition (18.25%). 266 fish were found on conservation partnership site, while only 187 fish found in off-site conservation partnership. In economic perspective, there are an increase in people. In social point, the existence of this conservation partnership program has raised awareness of the importance of coral reef ecosystems. From internal factors, the need for financial aid is essential to encourage people to start the conservation partnership program, while in external factors, better regulation from the local government will motivate people to join the program.